Penampilan Kedelai (Glycine max L. Merrill) Varietas Tanggamus pada Aplikasi Mikoriza Vesikular Arbuskular (MVA) dan Pupuk SP36 - Widiati, Bibiana Rini; Haerul,; Kumalawati, Zahraeni; Fitrah, Ahmad (Journal Galung Tropika, 2025)
The provision of mycorrhizal fungi makes phosphorus available in the soil because mycorrhizae play a role in dissolving phosphorus bound to the soil. Soybeans need phosphorus, a significant limiting factor for plant growth and production. The study aims to determine the optimal dose of vesicular-arbuscular mycorrhizal (VAM) inoculation and SP36 fertilizer on Tanggamus soybean varieties. The study was arranged using a Split Plot Design (RPT), with the main plot, namely the MVA dose consisting of 4 levels, namely: without mycorrhiza (m0), mycorrhiza 5 g.plant-1 (m1), 10 g.plant-1 (m2), 15 g.plant-1 (m3); and the subplot is SP36 fertilizer consisting of 4 levels, namely: Without SP36 (f0), SP36 7.7 g.plant-1 (p1), 11.5 g.plant-1 (p2), 15.4 g.plant-1 (p3). There were 16 treatment combinations consisting of 3 replications and 48 experimental units. The variables observed were plant height, root fresh weight, shoot fresh weight, flowering days, number of seeds per plant, and seed weight per plant. The results showed that the treatment of vesicular-arbuscular mycorrhiza 15 g.tan-1 with SP36 fertilizer 7.7 g.tan-1 increased growth, especially at a plant height of 50.68 cm (4.84%) and increased soybean plant yields, as shown by seed weight of 52.33 g.tan-1 (60.18%) compared to the treatment of SP36 fertilizer without mycorrhizas (15.4 g.tan-1).